Effectiveness of Baricitinib in Refractory Seronegative Rheumatoid Arthritis and Uveitis: A Case Report - Kaneko, Yutaka; Murakami, Takanori; Nishitsuka, Koichi; Takakubo, Yuya; Takagi, Michiaki; Yamashita, Hidetoshi (Frontiers in Medicine, 2022)
Baricitinib is a Janus kinase (JAK) inhibitor used in the treatment of refractory rheumatoid arthritis and blocks the subtypes JAK1 and JAK2. A 35-year-old man with seronegative rheumatoid arthritis complicated by bilateral severe non-granulomatous panuveitis was resistant to steroid treatment, multiple conventional disease-modifying antirheumatic drugs (methotrexate and salazosulfapyridine) and anti-TNF-alpha inhibitors (adalimumab and infliximab). Therefore, anti-TNF-alpha inhibitors was switched to baricitinib to decrease the activity of systemic arthritis. Then, along with the amelioration of inflammatory activity of seronegative rheumatoid arthritis, the inflammatory activity of uveitis was decreased. Vitreous opacity, serous retinal detachment and anterior chamber cells showed improvement. Baricitinib was effective not only in refractory systemic arthritis, but also in uveitis, which may provide a new treatment option for patients affected with refractory uveitis.